2013
DOI: 10.1242/jcs.116434
|View full text |Cite|
|
Sign up to set email alerts
|

Specific roles of Gi protein family members revealed by dissecting SST5 coupling in human pituitary cells

Abstract: SummaryDespite intensive investigation over the past 20 years, the specific role played by individual Gi protein family members in mediating complex cellular effects is still largely unclear. Therefore, we investigated the role of specific Gi proteins in mediating somatostatin (SS) effects in somatotroph cells. Because our previous data showed that SS receptor type 5 (SST5) carrying a spontaneous R240W mutation in the third intracellular loop had a similar ability to inhibit intracellular cAMP levels to the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In somatotroph cells, SRIF regulation of K C currents are mediated by Ga i3 (Chen 1997), while Ca 2C currents are mediated by Ga o2 (Chen 1997, Degtiar et al 1997), b1, b3 (Kleuss et al 1992), and g3 (Kleuss et al 1993. In human GH-secreting tumor cultures, sst5-specific signaling is dependent on Ga o1 (Peverelli et al 2013). SRIF-mediated inhibition of corticotropinreleasing hormone (CRH)-stimulated Ca 2C levels in human corticotropin-secreting pituitary adenomas is Petersenn et al (1999) and van der Hoek et al…”
Section: Cmentioning
confidence: 99%
See 3 more Smart Citations
“…In somatotroph cells, SRIF regulation of K C currents are mediated by Ga i3 (Chen 1997), while Ca 2C currents are mediated by Ga o2 (Chen 1997, Degtiar et al 1997), b1, b3 (Kleuss et al 1992), and g3 (Kleuss et al 1993. In human GH-secreting tumor cultures, sst5-specific signaling is dependent on Ga o1 (Peverelli et al 2013). SRIF-mediated inhibition of corticotropinreleasing hormone (CRH)-stimulated Ca 2C levels in human corticotropin-secreting pituitary adenomas is Petersenn et al (1999) and van der Hoek et al…”
Section: Cmentioning
confidence: 99%
“…In addition, PTX attenuated SRIFdependent inhibition of GHRH-induced GH in MtT/SGL somatotroph cells (Morishita et al 2003). sst5-specific inhibition of forskolin-stimulated cAMP accumulation was dependent on Ga o1 in human GH-secreting tumor primary cultures (Peverelli et al 2013). In AtT-20 cells, SRIF inhibition of adenylate cyclase and ACTH secretion is Ga i1 -dependent (Tallent & Reisine 1992).…”
Section: Cmentioning
confidence: 99%
See 2 more Smart Citations
“…coupled to inhibitory G proteins that reduce cAMP formation by inhibiting adenylyl cyclase activity, it has recently been demonstrated that SST5, the most expressed SS receptor subtype in pituitary together with SST2, exerts its antiproliferative effects in somatotrophs by coupling with the inhibitory G protein Go A , independently of cAMP reduction (Peverelli et al 2009b(Peverelli et al , 2013.…”
Section: In Vivo Phenotype Of Gsp Mutations: Counteracting Mechanismmentioning
confidence: 99%